Association of SNPs in nAChRs genes, areca nut chewing and smoking, and their interaction with lung cancer in Hainan, China: a case control study - Yixuan Li; Jing Zhou; Lirong Liu; Chaoyong Zhu; Ziyue Luo; Na Li; Pengfei Lyu; Jing Zhang; Tian Xie; Yipeng Ding; Sha Xiao (BMC Cancer)
Abstract Background Areca nut (AN) was classified as a carcinogen by the International Agency for Research on Cancer (IARC) of the WHO in 2003. AN has the same carcinogenic components as cigarettes, such as benzo[a]pyrene (B[a]P) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), but its effects on interactions with genetic factors related to lung cancer have rarely been investigated.  Methods Here, a propensity score-matched case‒control study was conducted in Hainan, which included 445 patients with lung cancer and 445 cancer-free controls. Then, the associations between single-nucleotide polymorphisms (SNPs) in the CHRNA5-CHRNA3-CHRNB4 gene cluster and their interaction effects with AN chewing and smoking on lung cancer were analyzed. In addition, we explored the associations among AN, cigarettes, and genes related to lung cancer using the Comparative Toxicogenomics Database (CTD). Results The results indicate that the CHRNA3 rs938682 (A > G) GG genotype (OR = 0.669, 95% CI = 0.454 ~ 0.984, P = 0.042) can decrease the risk of lung cancer. The CHRNB4 rs7178270 (C > G) GG genotype (OR = 1.729, 95% CI = 1.168 ~ 2.571, P = 0.006) can increase the risk of lung cancer. The CHRNA5 rs17486278 CC genotype was associated with a high risk in males, smokers, and drinkers. The CHRNA3 rs938682 GG genotype was associated with a low risk in AN chewers. The CHRNB4 rs7178270 GG genotype was associated with high risk in drinkers and AN chewers. CHRNB4 rs7178270 and AN chewing have an interaction effect on lung cancer in Hainan. Conclusions This study is the first to elucidate the hidden impacts of AN on lung cancer and provides a key evidence regarding the interactive effects of AN and cigarettes with SNPs in nAChRs genes on lung cancer. Graphical Abstract